Proceedings of the 3rd J-Parc Symposium (J-Parc2019) 2021
DOI: 10.7566/jpscp.33.011094
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion of Aluminum-based Containers for Neutron Studies with Aqueous Samples under Low Temperatures

Abstract: Quasielastic neutron scattering studies frequently employ aluminum (Al) or Al alloys as sample cells. Due to the increasing incident-neutron flux, this research area has experienced continuous expansion; thus, the rate of acquiring data for dilute conditions has increased considerably. One such research topic is water-containing systems. In this study, we investigated the effect of temperature on Al and found that Al corrosion occurs even in a low temperature atmosphere. This was attributed to the different th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Figure 1 a shows S ( Q , E ) of the D 2 O-Boehmite coated Al cell at −0.01 < Δ E meV < 0.02, plotted on average at 0.13 < Q Å −1 < 1.7 after subtracting the background profile of the instrument and correcting for detector efficiency using a vanadium standard, and the profiles of an H 2 O-Boehmite coated cell and an untreated cell were also appended to the graph as references. Owing to the fact that the boiling times for the boehmite treatment with H 2 O [ 27 , 28 ] and D 2 O are 1 h and 15 h, respectively, the thickness of the formed boehmite film based on the literature values can be estimated to be roughly 0.5 µm and 6.5 µm [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 1 a shows S ( Q , E ) of the D 2 O-Boehmite coated Al cell at −0.01 < Δ E meV < 0.02, plotted on average at 0.13 < Q Å −1 < 1.7 after subtracting the background profile of the instrument and correcting for detector efficiency using a vanadium standard, and the profiles of an H 2 O-Boehmite coated cell and an untreated cell were also appended to the graph as references. Owing to the fact that the boiling times for the boehmite treatment with H 2 O [ 27 , 28 ] and D 2 O are 1 h and 15 h, respectively, the thickness of the formed boehmite film based on the literature values can be estimated to be roughly 0.5 µm and 6.5 µm [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Considering the incoherent cross-section of hydrogen and deuterium (H: 82.02 barn, D: 2.05 barn) and the estimated thickness of the D 2 O-Boehmite, this result is reasonable; furthermore, it was found that the H contamination in the D 2 O-Boehmite was small. The boehmite coatings can be expected to provide corrosion resistance even in the case of thin films [ 28 , 29 ]. However, in QENS experiments that require measurements over long periods of time, especially under high temperatures, the boehmite may form using water in the aqueous solution samples.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations